Respostas
respondido por:
2
Bom dia Alice
(3x - 2)/4 - (4 - x)/2 = 2x - (7x - 2)/3
como os denominadores são diferentes precisamos de fazer o mmc
mmc(2,4,3) = 12
9x - 6 - 24 + 6x = 24x - 28x + 8
15x - 30 = -4x + 8
19x = 38
x = 2
(3x - 2)/4 - (4 - x)/2 = 2x - (7x - 2)/3
como os denominadores são diferentes precisamos de fazer o mmc
mmc(2,4,3) = 12
9x - 6 - 24 + 6x = 24x - 28x + 8
15x - 30 = -4x + 8
19x = 38
x = 2
Perguntas similares
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás